2018
DOI: 10.1590/1413-81232018238.23612016
|View full text |Cite|
|
Sign up to set email alerts
|

Does the type of sedentary behaviors influence blood pressurein adolescents boys and girls? A cross-sectional study

Abstract: The aim of this study was to analyze the association between different sedentary behaviors and high blood pressure in adolescent boys and girls. We conducted a cross-sectional study with 6,264 Brazilian adolescents (14 to 19 years old). Demographic data, obesity indicators and blood pressure, were evaluated. Time spent in the sedentary behaviors (television viewing, playing video games, using the computer, non-screen sitting and, total time sitting) were also assessed. The girls spent more time watching televi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(28 reference statements)
0
6
0
3
Order By: Relevance
“…Yin and colleagues, on the other hand, besides reporting a relation between sitting time and higher odds for abdominal obesity in a school-based sample of Chinese children and adolescents (6y -14y), found no association between sitting time and the odds for MetS (33). Similarly, Oliveira and colleagues found that sitting time was not associated with obesity indicators or blood pressure in a Brazilian sample of 6264 adolescents (14y -19y) (34).…”
Section: Discussionmentioning
confidence: 97%
“…Yin and colleagues, on the other hand, besides reporting a relation between sitting time and higher odds for abdominal obesity in a school-based sample of Chinese children and adolescents (6y -14y), found no association between sitting time and the odds for MetS (33). Similarly, Oliveira and colleagues found that sitting time was not associated with obesity indicators or blood pressure in a Brazilian sample of 6264 adolescents (14y -19y) (34).…”
Section: Discussionmentioning
confidence: 97%
“…A obesidade infantil vem apresentando dados cada vez mais alarmantes, preocupando a saúde pública, pois a obesidade é fator condicionante para o surgimento de diabetes, problemas respiratórios, cardiovasculares, e também em piora da qualidade de vida (LIBRELÃO; DINIZ, 2017), vem crescendo o número de obesidade infantil, devido a introdução precoce de alimentos inadequados, como os industrializados e processados com isso potencializa o risco para o desenvolvimento de obesidade infantil (OLIVEIRA et al, 2018).…”
Section: )unclassified
“…A elevada prevalência de adolescentes expostos ao tempo excessivo de tela causa preocupação devido a associação com diversos problemas de saúde, como excesso de peso corporal, alterações na glicose e colesterol sanguíneos, baixo rendimento escolar e diminuição do convívio social e menores níveis de atividade física, além de reflexos na percepção corporal (SISSON et al 2010;TREMBLAY 2011). Destaca-se ainda que esse hábito na adolescência possa ser transferido à idade adulta (OLIVEIRA, 2018).…”
Section: Introductionunclassified
“…HTN in childhood is associated with early cardiovascular events like congestive heart failure (CHF), left ventricular hypertrophy (LVH), and increased morbidity and mortality in adulthood [ 4 , 5 ]. Affecting more than 2.5–17.3% of adolescents [ 6 ], HTN in childhood and adolescence is described to track into adulthood and is associated with major cardiovascular problems such as heart failure, stroke, and congestive heart disease [ 1 , 7 ]. In recent years, the increasing prevalence of HTN among children and adolescents in numerous areas has been a major concern [ 1 , 8 ], which highlights the further need for health-related interventions.…”
Section: Introductionmentioning
confidence: 99%